Computed Tomography Honeycombing Identifies a Progressive Fibrotic Phenotype with Increased Mortality across Diverse Interstitial Lung Diseases - Adegunsoye, Ayodeji (Ann Am Thorac Soc, 2019)
Rationale: Honeycombing on chest computed tomography (CT) has been described in diverse forms of interstitial lung disease (ILD); however, its prevalence and association with mortality across the spectrum of ILD remains unclear. Objective: To determine the prevalence and prognostic value of CT honeycombing and characterize associated mortality patterns across diverse ILD subtypes in a multicenter cohort. Methods: This was an observational cohort study of adult participants with multidisciplinary or adjudicated ILD diagnosis and documentation of chest CT imaging at index diagnosis across five U.S. hospitals (one tertiary and four nontertiary medical centers). Participants were stratified based on presence or absence of CT honeycombing. Vital status was determined from review of medical records and social security death index. Transplant-free survival was analyzed using univariate and multivariable Cox regression. Results: The sample comprised 1,330 participants (mean age, 66.8 yr; 50% men) with 4,831 person-years of follow-up. The prevalences of CT honeycombing were 42.0%, 41.9%, 37.6%, and 28.6% in chronic hypersensitivity pneumonitis, connective tissue disease–related ILD (CTD-ILD), idiopathic pulmonary fibrosis (IPF), and unclassifiable/other ILDs, respectively. Among those with CT honeycombing, cumulative mortality hazards were similar across ILD subtypes, except for CTD-ILD, which had a lower mortality hazard. Overall, the mean survival time was shorter among those with CT honeycombing (107 mo; 95% confidence interval [CI], 92–122 mo) than those without CT honeycombing (161 mo; 95% CI, 147–174 mo). CT honeycombing was associated with an increased mortality rate (hazard ratio, 1.72; 95% CI, 1.38–2.14) even after adjustment for center, sex, age, forced vital capacity, diffusing capacity, ILD subtype, and use of immunosuppressive therapy (hazard ratio, 1.62; 95% CI, 1.29–2.02). CT honeycombing was associated with an increased mortality rate within non-IPF ILD subgroups (chronic hypersensitivity pneumonitis, CTD-ILD, and unclassifiable/other ILD). In IPF, however, mortality rates were similar between those with and without CT honeycombing. Conclusions: CT honeycombing is prevalent in diverse forms of ILD and uniquely identifies a progressive fibrotic ILD phenotype with a high mortality rate similar to IPF. CT honeycombing did not confer additional risk in IPF, which is already known to be a progressive fibrotic ILD phenotype regardless of the presence of CT honeycombing.